Pengaruh beberapa perlakuan penyimpanan terhadap perkecambahan benih suren (Toona sureni) - Hery Suryanto (Jurnal Penelitian Kehutanan Wallacea, 2013)
Wood of Suren (Toona sureni) has a good reputation for wood quality for various uses including building materials, plywood, container and furniture. Therefore this species is preferred for plantation development. Seed is important on planting material for establish forest plantation. The characteristics of seeds are hygroscopic and depending on the factors of relative air humidity and the temperature of environment where the seeds are stored. This research was aimed to evaluate the effect of storage temperature on seed quality of suren which was stored on seed (after extraction) and on fruit (before extraction). The study was arranged in a Factorial Completely Randomized Design with pattern of 3 factors and 3 replications. The first factor is room storage at room temperature and Dry Cold Storage (DCS), the second factor of packaging materials were paper, cloth, aluminum foil, and plastic. The third factor was the storage period of 0, 2, 4, and 6 weeks. Each treatment consisted of three replications, as many as 50 seeds of each. The parameters used were water content (%) and germination (%). The result were observed showed that aluminum foil packaging at room temperature until 4 weeks was able to store seeds of suren properly and efficiently in which the water content was stable from 6.11% to 10.82% with 71% germination rate.